2013
DOI: 10.1097/iae.0b013e3182618c22
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Acute Changes in Systolic Blood Pressure Do Not Alter Choroidal Thickness as Measured by a Portable Spectral-Domain Optical Coherence Tomography Device

Abstract: Purpose To measure choroidal thickness in patients manifesting an acute change in systemic arterial blood pressure using a portable spectral-domain optical coherence tomography device (iVue). Methods Fifteen patients (15 eyes) undergoing cardiac exercise stress testing were scanned using a portable spectral-domain optical coherence tomography system (iVue). Two scan protocols were used: cross line scan for measuring choroidal thickness and the retina map scan to measure retinal thickness. Each patient was sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 24 publications
4
28
2
Order By: Relevance
“…There were no significant changes in the mean CCT before and after the exercise which is consistent with recent reports [2, 13]. Our results added the new information that there were no significant changes in the mean total choroidal area, the mean luminal and stromal areas after the dynamic exercise.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There were no significant changes in the mean CCT before and after the exercise which is consistent with recent reports [2, 13]. Our results added the new information that there were no significant changes in the mean total choroidal area, the mean luminal and stromal areas after the dynamic exercise.…”
Section: Discussionsupporting
confidence: 93%
“…The results of a recent study using the enhanced-depth imaging optical coherence tomography (EDI-OCT) showed that there was a significant increase in the choroidal thickness after exercise [12], but others did not find any significant changes in the thickness after the exercise [2, 13]. Because the choroid does not have a distinct layer-by-layer architecture, the changes of either the luminal or stromal areas of the choroid after exercise have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the choroidal response to stress tests in healthy subjects and in CSCR patients by measuring the choroidal thickness with Spectral Domain OCT and enhanced depth imaging. 47,48 Alwassia et al 47 did not obtain any significant change in choroidal thickness during an acute increase of systolic BP in healthy subjects. Roybal et al 48 observed an increase of choroidal thickness as a response to increased BP in patients with CSCR but not in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, smoking can cause temporary changes in CT, but it has also been demonstrated that CT is not significantly associated with smoking [7,8]. Additionally, there is another study that shows that CT is not significantly associated with blood pressure [9]. There is only one study in the literature that has investigated choroidal thickness changes during the menstrual cycle [10].…”
Section: Dear Editormentioning
confidence: 96%